Exploring the Interaction Mechanism Between Cyclopeptide DC3 and Androgen Receptor Using Molecular Dynamics Simulations and Free Energy Calculations - Zhang, Huimin; Song, Tianqing; Yang, Yizhao; Fu, Chenggong; Li, Jiazhong (Frontiers in Chemistry, 2018)
Androgen receptor (AR) is a key target in the discovery of anti-PCa (Prostate Cancer) drugs. Recently, a novel cyclopeptide Diffusa Cyclotide-3 (DC3), isolated from Hedyotisdiffusa, has been experimentally demonstrated to inhibit the survival and growth of LNCap cells, which typically express T877A-mutated AR, the most frequently detected point mutation of AR in castration-resistant prostate cancer (CRPC). But the interaction mechanism between DC3 and AR is not clear. Here in this study we aim to explore the possible binding mode of DC3 to T877A-mutated AR from molecular perspective. Firstly, homology modeling was employed to construct the three-dimensional structure of the cyclopeptide DC3 using 2kux.1.A as the template. Then molecular docking, molecular dynamics (MD) simulations and molecular mechanics/generalized Born surface area (MM-GBSA) methods were performed to determine the bind site and explore the detailed interaction mechanism of DC3-AR complex. The obtained results suggested that the site formed by H11, loop888-893 and H12 (site 2) was the most possible position of DC3 binding to AR. Besides, hydrogen bonds, hydrophobic and electrostatic interactions play dominant roles in the recognition and combination of DC3-AR complex. The essential residues dominant in each interaction were specifically revealed. This work facilitates our understanding of the interaction mechanism of DC3 binding to AR at the molecular level and contributes to the rational cyclopeptide drug design for prostate cancer.